Description of eight new species of the genus Irepacma Moriuti, Saito & Lewvanich (Lepidoptera: Autostichidae) from China - Wang, Shuxia; Xu, Zhixin; Li, Suran (Zootaxa, 2022)
Eight new species of the genus Irepacma Moriuti, Saito & Lewvanich, 1985 are described based on specimens collected in China: I. bispicifera Wang, sp. nov., I. curticylindra Wang, sp. nov., I. denticulata Wang, sp. nov., I. flaviptera Wang, sp. nov., I. longiflagellata Wang, sp. nov., I. rotunda Wang, sp. nov., I. spiculosa Wang, sp. nov., I. tengchongensis Wang, sp. nov. Periacma isomora Meyrick, 1910 is transferred to the genus Irepacma: I. isomora (Meyrick, 1910), comb. nov. Images of adults and genitalia are provided.